Development of Waqf properties in Malaysia with reference to Waqf Ahmad Dowjee Dadabhoy and Wakaf Seetee Aisah - Mohamad, Nor Asiah (2019)
The presentation shares on two types of successful model for Waqf Development. The study focuses on Ahmad Dowjee Waqf which employ Built Operate and Transfer (BOT) and Wakaf Seetee Aisah which adopts joint venture between GLC and MAINS